THE IMPACT OF ATP-BINDING CASSETTE SUBFAMILY B MEMBER 1 (ABCB1) POLYMORPHISMS ON STANDARD TREATMENTS FOR SYSTEMIC LUPUS ERYTHEMATOSUS - Muhammad Syawal Pratama; Laniyati Hamijoyo; Melisa I. Barliana (Fakultas Farmasi, Universitas Padjadjaran, 2020)
The ATP-Binding Cassette Subfamily B Member 1 (ABCB1) gene encodes for P-glycoprotein (P-gp) which is an efflux pump used to transport a variety of xenobiotics. The role of ABCB1 polymorphisms in Systemic Lupus Erythematosus (SLE) affect outcomes of standard therapy (hydroxychloroquine, glucocorticoid (GC), azathioprine (AZA), mycophenolate mofetil (MMF), and cyclophosphamide (CYC)). We conducted an investigation assessing affiliations between the ABCB1 polymorphisms, G1199A, C1236T, G2677T/A, and C3454 and effectiveness variables. Although ABCB1 polymorphisms do not cause SLE, they exert a significant impact on therapy effectiveness. These polymorphisms significantly influenced GCs and AZA, had less effects on methotrexate (MTX), MMF, and CYC, and no impact on antimalarials. The four most influential polymorphisms were, rs1045642 (C3454), rs1128503 (C1236T), rs2032582 (G2677T/A), and rs2229109 (1199A).